Beating heart partial ventriculectomy in dogs - Aguiar, Eduardo Santiago Ventura de; Schossler, João Eduardo Wallau; Raiser, Alceu Gaspar; Ferreira, Alessandra Quaresma; Kirst, Claudia; Pellizzari, Mariana Lopes; Spagnol, Camila; Cavalcanti, Ruben Lundgren; Souza, Eduardo Martins; Mucillo, Marcelo de Souza; et al. (Acta Scientiae Veterinariae, 2018)
After valve endocardiosis, dilated cardiomyopathy is the most diagnosed cardiac affection in dogs. Sometimes this disease is unresponsible to medical therapy, in this way surgery becomes necessary to its correction. Unfortunately, dogs do not support cardiopulmonary bypass because its tendency in microtrombus formation in the capillary vessels of the lung circulation. Due to this condition, another surgical alternatives were developed, in order to correct the increase in ventricle size, as the ventricle plication or partial ventriculectomy with the inflow occlusion. However, this kind of technique has its complications, as well the ventricle plication. In plication, a part of necrotic heart tissue still remains, and if the necrosis does not happen, that portion of myocardium keeps its oxygen consumption, leading to heart failure. The partial ventriculectomy with the inflow occlusion is time dependent. For its execution it means that the surgeon gets only four minutes to perform the resection of the dilated ventricle and then suture the remaining defect after the inflow occlusion. The aim of this study is to develop a new technique of heart size reduction, called by the authors Beating Heart Partial Ventriculectomy.